The Effect of Leverage and Political Connections on the Performance of State-Owned Enterprises - Latif, Rahmawati; Usmany, Paul; Sososutiksno, Christina (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine the influence of leverage and political connections on the performance of state-owned enterprises (SOEs) with good corporate governance (GCG) as a moderating variable. The research uses a quantitative approach, with the population consisting of SOEs listed on the Indonesia Stock Exchange (IDX). The sample was selected using purposive sampling, resulting in 13 companies being chosen as the study's subjects. The results of the study indicate that leverage negatively affects company performance, meaning that the higher a company's debt, the lower its performance. Conversely, political connections have a positive impact on performance, suggesting that political involvement can provide advantages in enhancing a company's performance. Additionally, good corporate governance is found to positively influence company performance, reinforcing the importance of sound governance in supporting operational success. Good corporate governance also acts as a moderating variable. GCG weakens the negative relationship between leverage and company performance, while strengthening the positive impact of political connections on performance. This indicates that strong governance practices can help mitigate the adverse effects of high leverage and maximize the benefits of political connections that the company may have.